Pengaruh Lokasi, Kualitas Pelayanan dan Persepsi Harga Terhadap Kepuasan Konsumen Kopi Jaksa Dikota Bengkulu - Putri Apriani; Arifah Hidayati; Syofian (Economic Reviews Journal, 2024)
The purpose of this study was to determine and analyze the effect of location, service quality and price perception on consumer satisfaction of Bengkulu City Attorney Coffee. In this study using non-probability sampling techniques, a sample of 90 respondents was taken. Data was taken using a questionnaire measured on a Likert scale. This study uses multiple linear regression analysis with the help of the SPSS version 22 program in 2024, the results of this study indicate that location has an effect on consumer satisfaction but service quality and price perceptions have a partial effect on consumer satisfaction. The results also show that location, service quality and price perception simultaneously affect customer satisfaction.